Quantitative modelling of endocrine diseases as exemplified by diabetes. - Turner, R; Rudenski, A; Holman, R; Matthews, DR; O'Rahilly, S (1987)
The feedback loops between glucose and insulin have as fundamental a role in diabetes as do the regulatory feedback loops affected in other endocrine disorders. In contrast to other endocrine diseases, diabetes mellitus is rarely investigated by measuring the key hormone, insulin. This is because both the stimulatory and inhibitory control points of the feedback lop areo effected, rendering interpretation of plasma glucose and insulin levels difficult. The application of a mathematical model of glucose-insulin interaction can provide a frame of reference which allows the feedback loop can be assessed from fasting plasma insulin and glucose concentrations alone and this analysis has been termed 'homeostasis model assessment' (HOMA). Similar analysis has been suggested for thyroid and parathyroid disease. Minimal stressing of the feedback loop by a continuous infusion of glucose re-sets the homeostatic control at higher glucose and insulin concentrations allowing more precise measurement, and this 'continuous infusion of glucose with model assessment (CIGMA)' has been used to show that the initial detectable lesion in familial Type II diabetes is deficient β-cell function rather than impaired insulin sensitivity. When hormone assays do not provide an immediately clearcut diagnosis in other endocrine disorders, similar mathematical modelling might help to detect and quantify mild and/or interacting deficits at different control points.